Kepentingan Ekspansi “Trans Mountain Pipeline” Kanada Tahun 2019 Selama Komitmen Net-Zero Emission 2050 - Pramesswari, I Gusti Ayu Ririn; Wiranata, I Made Anom; Parameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2025)
This research aims to examine Canada's interests in the Trans Mountain Pipeline Expansion policy and on the one hand also tries to fulfill its commitment to the Paris Agreement for Net Zero Emissions 2050. The research method used in this research is a quantitative research method using literature study research techniques. This method was chosen so that the research focus could be carried out in more depth. This research uses Realism theory in looking at energy security, economic interests, and international agreements regarding climate change. With this method, researchers can determine journals, news and data that can be used to write a thesis. In conclusion, the researcher succeeded in finding the answer to the research problem  formulation. The decision to approve the Trans Mountain Pipeline expansion project is Canada's energy strategy to protect energy security and reduce dependence on oil imports from other countries. Having access and control over national (domestic) energy resources is key to ensuring energy security. Furthermore, in response to the lack of oil pipeline infrastructure which limits access to more diverse markets, namely access to markets in developing countries in the Pacific Rim, especially Asia and access to global markets. Economic interests are also something that Canada wants to achieve because the oil industry has a significant contribution to Canada's Gross Domestic Product. Canada remains involved in global environmental agreements such as the Paris Agreement, to be able to build a positive image in international relations. Keywords : Canada, Energy Security, Paris Agreement, Realism, Trans Mountain Pipeline